The Impact of Founder’s Financial Behavior Traits and Literacy on SMEs Performance: Empirical Evidence from SMEs in Indonesia - Nakita Gusman; Subiakto Soekarno; Isti Raafaldini Mirzanti (Jurnal Keuangan dan Perbankan, 2021)
This research focuses on the SMEs development evaluation of the impact of founder’s financial behavior, measured by behavioral characteristics of CEOs capacity for self-awareness, planning, and patience, also their knowledge about financial understanding which affect the ability to manage their performance of SMEs. The purpose of this research is to analyze and reduce the rate of failure of SMEs in Indonesia by pursuing the defined determinants from their behavioral traits and self-knowledge on financial understanding in decision making. This study uses a survey conducted across Indonesia, mainly on Java island, with the sample size of 482 SMEs. This research uses multivariate regression analysis as a tool for measuring the impact of founder’s financial behavior variables and financial literacy variable for SMEs performance as a dependent variable. DOI: 10.26905/jkdp.v25i3.5142